Knowledge and attitude towards vaccine preventable diseases and vaccination among prospective malaysian hajj pilgrims in Klang Valley, Malaysia - Tan Z.H.; Zamli F.N.A.M.; Izal L.H.M.; Joseph N.; Nordin S.A.; Nurul Azmawati Mohamed @ Abd Aziz (Universiti Putra Malaysia Press, 2024)
Indexed by Scopus/MyCite